Identification and evaluation of barriers and drivers to sustainable construction in China - Sajjad, M. (Institute of Electrical and Electronics Engineers Inc., 2021)
The rapid economic development of China is also a threat to environmental sustainability, there is an urgent need to boost the environment friendly construction to cope with the rising issues. In this regard, a questionnaire-based survey was conducted to identify and evaluate the major barriers and drivers to sustainable construction (SC) in China. Moreover, SC experts were interviewed to get an insight of where these barriers are likely to cause hinderance during the construction phases and where the drivers can help up to some extent to tackle the problems. The overall aim of the research was to identify barriers that need to be overcome so that progress can be made towards the adoption of sustainable development. The results show that, lack of clear benefits from SC; lack of technical knowledge or trainings; concerns about durability and performance; affordability or financing; and de-lay in decision making; are the top five barriers with extremely high impact to slowdown the race towards sustainability in construction. On the other hand, financial incentives; more demonstration on policies and procedures; developing regulatory mechanism; client demand; and legislation or legal requirement; are the top five drivers which can spur the green buildings construction in China. Â© 2021 IEEE.